PIBID e a formaçâo inicial de professores de educação física - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The purpose of the present study is to investigate the repercussions of the Institutional Program for Teaching Initiation Scholarships (PIBID) in teacher training, from the point of view of scholarship students from the Physical Education Degree Course at UNIPAMPA. Currently the degree in Physical Education at UNIPAMPA has thirty scholarships for initiation to teaching (ID), two coordinators and six supervisors of basic education who develop actions in five public schools in Uruguaiana with the objective of valuing and strengthening the teaching of Physical Education. Information was collected through interviews with ID Physical Education fellows. In this report, emphasis is placed on teacher training based on the articulation between university and school, aiming at improving the quality of education, as well as the insertion of undergraduate students in Physical Education at school, enabling the exchange of knowledge. The Program benefits the creation of a space for the construction of new knowledge, produced in the relationships between institutions and subjects, integrating the different types of knowledge that make up professional knowledge.
PIBID and the initial training of physical education teachers
Keywords: PIBID; Formação docente; Formação inicial; Educação física; Physical education; Teacher training; Initial formation; CNPQ::CIENCIAS DA SAUDE